The impact of life cycle stage on firm acquisitions. Issue 2 (2nd March 2020) - Ames, Daniel; Coyne, Joshua; Kim, Kevin
Abstract : Purpose: The purpose of the authors' research study is to identify the impact of life cycle stage on firm acquisitions. Design/methodology/approach: The authors use a series of empirical databases to identify characteristics of acquirers and their targets. The authors then use logistic regressions and joint tests to identify significant differences between declining and non-declining acquirers. Findings: The authors find that declining acquirers are more likely to pursue diversifying acquisitions and to pay for the acquisition with stock considerations. Acquisitions by declining acquirers result in positive abnormal returns initially, but post-acquisition returns are negative. Research limitations/implications: The authors' primary limitation is their data, which only includes public acquirers and targets, and runs from January 1, 1988 to December 31, 2010. Practical implications: The authors' research suggests that regulators, stakeholders and prospective stakeholders should consider the life cycle stage of an acquiring firm in setting expectations about motivations for and likely performance subsequent to the acquisition. Originality/value: The authors' paper is the first to consider the effect of firm life cycle stage on the motivation and subsequent success of an acquisition. Given the tremendous impact to shareholders of such significant transactions, understanding the acquisition process more completely is important to capital markets participants.